Comorbid anxiety and depression: a community-based study examining symptomology and correlates during the postpartum period. (20th October 2019) - Ramakrishna, Sandhya; Cooklin, Amanda R.; Leach, Liana S.
ABSTRACT: Background : Despite indications that anxiety and depression co-occur frequently within the postpartum period, studies identifying the correlates associated with this comorbidity are rare. Objective : This study assessed variation in social and maternal circumstances, based on comorbid anxiety and depression symptomology. Methods : A large community-based sample of 1070 Australian postpartum women completed the Living with a Young Baby online survey. Mothers were categorised into groups: (a) comorbid anxiety and depression symptomology, (b) anxiety only, (c) depression only, or (d) neither depression nor anxiety. Multinomial Logistic Regression (MLR) investigated variation in correlates between the groups. Results : Comorbid anxiety and depression symptomology was common (13.4%), and was associated with greater symptom severity. Women in the 'comorbid' group more often experienced financial hardship, cessation of breastfeeding, infants with difficult temperaments, inadequate social support or help, and stressful adverse life events in comparison to mothers in the 'neither symptomology' group. They were also more likely to have infants with difficult temperaments compared to the depression only group, and to receive inadequate help and support compared to the anxiety only group. Conclusions : Comorbid anxiety and depression symptomology is common postpartum and is associated with considerable adversity across a wide range of demographic, economic and social correlates. Abbreviations: EPDS: Edinburgh Postnatal Depression Scale; STAI: State-Trait Anxiety Inventory; MLR: Multiple Logistic Regression; LYBS: Living with a Young Baby Survey; LSAC: Longitudinal Study of Australian Children; STSI: Short Temperament Scale for Infants; ANOVA: Analysis of Variance; M: Mean; SD: Standard Deviation; CI: Confidence Interval; OR: Odds Ratio